Selective modification of the β–β linkage in DDQ-treated Kraft lignin analysed by 2D NMR spectroscopy. Issue 1 (1st September 2014) - Tran, F.; Lancefield, C. S.; Kamer, P. C. J.; Lebl, T.; Westwood, N. J.
Abstract : Analysis of the selective transformation of the β–β linkage in Kraft lignin using readily accessible 2D HSQC NMR protocols. Abstract : The depolymerisation of the biopolymer lignin has the potential to provide access to a range of high value and commodity chemicals. However, research in this increasingly important area of green chemistry is hindered by the lack of analytical methods. The key challenge in using NMR is the throughput that can be achieved without the need for high field spectrometers fitted with cryoprobes. Here, we report the use of a relatively fast 2D HSQC NMR experiment performed on a 500 MHz spectrometer fitted with a BBFO+ probe to obtain high quality spectra. The use of the developed protocol to study the selective modification of the β–β linkage in Kraft lignin is also reported.